Hubungan Penguasaan Kosakata dengan Keterampilan Menulis Teks Narasi Siswa Kelas V SDN Gugus 1 Kecamatan Praya Tengah - Mira Naniy Salfiyani; Darmiany Darmiany; Syaiful Musaddat (Educational Consultant & Counseling Career (EC3) Mataram, 2021)
The study was intended to describe the mastery level of the student's vocabulary, describe the skill level of the text of the student narrative, and proving whether there was a vocabulary mastery relationship with writing skills of text narrative students class 5 (V) of SDN 1 of Central Praya predistrict year of 2020/2021. The study is a quantitative, correlated study. This research population meet the entire 5 class of students in the SDN 1 of Central Praya predistrict 134 apprentices. The sample used was proportional random sampling, therefore 67 students as a research sample. The data-gathering technique is a test of multiple selections and a narrative essay. The student narrative endescriptive level and skill writing the text of the student is analyzed using a descriptive analysis, and the testing of research hypotheses analyzed using a Pearson product moment clause. research indicates the student's vocabulary mastery level is in fairly good category with the average student value of 20.87, The level of textual writing skills of the student narrative is adequately rated with the student's overall value of 72.30 values r-counting 0.614 more than r-table 0.2369 at a significant 5% point which means there is a significant and a posite-between vocabulary mastery and narration skills class 5. Hence the detail. Vocabulary mastery was an essential aspect to develop and Note in supporting the process of students' learning more in the learning of the 5class of student narration text.